Perancangan Sistem Informasi Mushola Berbasis Web Menggunakan Metode Waterfall (Studi Kasus Mushola At-Taubah) - Pratama, Renaldi; Abisono Punkastyo, Dimas (CV. Shofanah Media Berkah, 2023)
At-Taubah Mosque is one of the mosques located in RW 05 Grogol, Depok. The number of activities in and out of finances and activities that occur makes the process of managing finances and activities difficult and takes a long time to record and search data because they are still using books so they are not computerized. On this basis, the design of a web-based prayer room information system was developed, so that it could facilitate the managers of the At-Taubah Mosque in managing the finances and activities of the mosque. In this application using the PHP programming language, where PHP is inserted into HTML is used to build a website application. As for the database management using MySQL. The application using Website media aims to make it easier for mosque managers to monitor financial management and prayer room activities, especially in receiving, issuing, and reporting finances and mosque activities. The research method carried out by the author in conducting research includes interviews, observations and literature studies. While the development uses the Waterfall method. The stages of this research include needs analysis, system design, implementation and testing. The design of the At-Taubah Mosque information system uses black box and white box testing methods. Based on these tests, all application functions have been running properly and optimally as they should.